Maintenance for Industrial Systems - Manzini, Riccardo; Regattieri, Alberto; Pham, Hoang; Ferrari, Emilio; SpringerLink (Online service) (London : Springer London, 2010)
New, global and extended markets are forcing companies to process and manage increasingly different products with shorter life cycles, low volumes and reduced customer delivery times. In today$1 (Bs global marketplace production systems need to deliver products on time, maintain market credibility, and introduce new products and services faster than competitors. As a result, a new production system paradigm has been developed and a supporting management decision-making approach, which simultaneously incorporates design, management, and control of the production system, is necessary in order for this challenge to be met effectively and efficiency. Maintenance for Industrial Systems addresses this need by introducing an original and integrated idea of maintenance: maintenance for productivity. The volume starts with the introduction and discussion of a new conceptual framework based on productivity, quality, and safety supported by maintenance. Subsequent chapters illustrate the most relevant models and methods for planning, organising, implementing and controlling the whole maintenance process. Several examples of problems supported by solutions, and real applications to help and test the reader$1 (Bs comprehension are included. Maintenance for Industrial Systems is a valuable source of information for engineering students, doctoral and post-doctoral students, and also for maintenance practitioners and managers of industrial or service companies. Springer Series in Reliability Engineering publishes high-quality books in important areas of current theoretical research and development in reliability, and in areas that bridge the gap between theory and application in areas of interest to practitioners in industry, laboratories, business, and government.s
A New Framework for Productivity in Production Systems -- Quality Management Systems and Statistical Quality Control -- Safety and Risk Assessment -- to Maintenance in Production Systems -- Basic Statistics and Introduction to Reliability -- Reliability Evaluation and Reliability Prediction Models -- Maintenance Information System and Failure Rate Prediction -- Effects Analysis and Reliability Modeling of Complex Production Systems -- Basic Models and Methods for Maintenance of Production Systems -- Advanced Maintenance Modeling -- Spare Parts Forecasting and Management -- Applications and Case Studies.
Keywords: Engineering; System safety; Engineering; Quality Control, Reliability, Safety and Risk